Factors Promoting Religious Socialization among Secondary Schools Students - Kainat, Warda; Buzdar, Muhammad Ayub (Pakistan Journal of Humanities and Social Sciences, 2023)
Religious socialization is an important debate in the field of social sciences and education psychology. Religion is an integral part of Pakistani society because Pakistan is an idealistic state. Therefore, it is important to study the factors that promote religious socialization among secondary school students. It gave clear dimensions about the emerging social trends in religious societies. This study aimed to critically analyze the factors promoting religious socialization and compare them. These factors include family, peers, school, government, religious places, mass media, and social media. For this analysis, a quantitative approach was used with a descriptive research design. The review of the related literature enables researchers to develop a questionnaire comprising 38 items. The population for the study was from secondary schools of district Jhang. The study consisted of 600 respondents from different schools with an equal ratio of male and female schools as well as rural and urban schools. The percentages were collected, tabulated, and compared. Results suggested that family was the most significant agent that promoted religious socialization among students at secondary schools. The independent sample t-test was used to compare the school and gender-wise religious socialization at secondary schools. The results of the present study show that there are many factors that play an important role in promoting religious socialization among students at secondary schools.